2021
DOI: 10.3390/jcm10184064
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Epidermal Growth Factor (EGF) as Candidate Biomarker of Mood Disorders—Longitudinal Study in Adolescent and Young Adult Patients

Abstract: Bipolar disorder (BD) is a chronic mental disorder that affects more than 1% of the population worldwide. Over 65% of patients experience early onset of the disease. Most cases of juvenile bipolar disorder begin with a depressed mood episode, and up to 50% of youth initially diagnosed with major depression go onto developing a BD. Our study aimed to find biomarkers of diagnosis conversion in young patients with mood disorders. We performed a two-year follow-up study on 79 adolescent patients diagnosed with MDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Some other potential markers of this Special Issue include the epidermal growth factor (EGF) at the onset of the exacerbation of depressive or hypomanic/manic episodes [33] and neutrophil-to-lymphocyte (NLR) ratio, which has been suggested for differentiating bipolar from unipolar depression [34]. In autism spectrum disorder (ASD), a physiological biomarker collected from a wearable sensor's data was found to be helpful in its differential diagnosis [35], and some augmentations were suggested to help in its treatment [36].…”
Section: Other Immune-related Markersmentioning
confidence: 99%
“…Some other potential markers of this Special Issue include the epidermal growth factor (EGF) at the onset of the exacerbation of depressive or hypomanic/manic episodes [33] and neutrophil-to-lymphocyte (NLR) ratio, which has been suggested for differentiating bipolar from unipolar depression [34]. In autism spectrum disorder (ASD), a physiological biomarker collected from a wearable sensor's data was found to be helpful in its differential diagnosis [35], and some augmentations were suggested to help in its treatment [36].…”
Section: Other Immune-related Markersmentioning
confidence: 99%
“…Since a recent report demonstrated that the applied here Human/Mouse BDNF DuoSet ELISA kit cross-reacts 100% with proBDNF [ 27 ] and therefore detects total BDNF (mature BDNF plus proBDNF), we additionally measured the effects of N-ADA and N-DDA on the levels of proBDNF under OS conditions using a specific proBDNF ELISA kit. In cell lysates, the predominant form of BDNF is mature BDNF (more than 97%).…”
Section: Resultsmentioning
confidence: 99%
“…Rat models have shown that EGF-treated rats can be used as animal models for psychiatric disorders due to changed behavior and/or cognitive dysfunctions ( Futamura et al, 2003 ). Studies has described increased serum levels of EGF in youth with depressive or hypomanic/manic episodes in bipolar disorders ( Skibinska et al, 2021 ). Thus, EGF's effect on cognitive functions is well described.…”
Section: Discussionmentioning
confidence: 99%